Influence of Information Management on Decision-Making among University Managers in Southern Nigeria - Ekejiuba, Paulette; Yamah, M. I. (NIU Journal of Social Sciences, 2024)
This study examined the influence of information management on the decision-making among university managers in Southern Nigeria. Four research questions were raised to guide the study. The population consisted of all the University managers in Southern Nigeria: Three hundred and twenty-five of the population was selected using multi-stage random sample technique. An instrument titled: “Information Management and Decision-making Practices” was used to collect data. Pilot study was used to validate the instrument while Pearson correlation (r) was used for the reliability of the instrument. Data collected was analysed using the descriptive Pearson (r) statistics. The findings showed that information was effectively managed which enhances effective decision-making among the university managers. The result again showed that there was significant relationship between information management and effective decision-making among university managers based on gender of the managers. Based on the findings of this study, it was recommended that broader awareness of information and practices may be valuable as the managers’ attempt to interpret behaviours in the fresh decision-making situations. Keywords: Information Management, Decision-Making, Electronic, Physical.